LARGE DETERMINANT OF GREENHOUSE GAS EMISSIONS DISCLOSURE IN INDONESIA - Suryani, Rohmah; Wijayati, Fitri Laela (Riset Akuntansi dan Keuangan Indonesia, 2019)
The purpose of this study is to examine the influence of corporate governance and financial performance toward the greenhouse gases disclosure. Study in the companies listed in Bursa Efek Indonesia (BEI) for the year 2014-2017.       This study used secondary data from sustainability report dan company?s annual report. The sampling technique used purposive sampling. Sample of this study consist by 13 companies in four year to 52 companies. Data was analyzed by multiple linier regression. As for data processing using SPSS.     The result of this study showed that environmental management system, environmental committee, leverage, and board independence has no effect to greenhouse gases disclosure. While profitability, capital expenditure, company size, and financial slack has effect positive and significant to greenhouse gases disclosure. Keywords: greenhouse gases disclosure, environmental management system, environmental committee, capital expenditure, financial slack.